Chemical Composition of Essential Oil from Citrus reticulata Blanco cv. Chachiensis (Chachi) and Its Anti-Mosquito Activity against Pyrethroid-Resistant Aedes albopictus - Jifan Cao; Wende Zheng; Baizhong Chen; Zhenping Yan; Xiaowen Tang; Jiahao Li; Zhen Zhang; Song Ang; Chen Li; Rihui Wu; Panpan Wu; Wen-Hua Chen (Insects, 2024)
The overuse of synthetic insecticides has led to various negative consequences, including insecticide resistance, environmental pollution, and harm to public health. This may be ameliorated by using insecticides derived from botanical sources. The primary objective of this study was to evaluate the anti-mosquito activity of the essential oil (EO) of Citrus reticulata Blanco cv. Chachiensis (Chachi) (referred to as CRB) at immature, semi-mature, and mature stages. The chemical compositions of the CRB EO were analyzed using GC-MS. The main components were identified to be D-limonene and γ-terpinene. The contents of D-limonene at the immature, semi-mature, and mature stages were 62.35%, 76.72%, and 73.15%, respectively; the corresponding contents of γ-terpinene were 14.26%, 11.04%, and 11.27%, respectively. In addition, the corresponding contents of a characteristic component, methyl 2-aminobenzoate, were 4.95%, 1.93%, and 2.15%, respectively. CRB EO exhibited significant larvicidal activity against Aedes albopictus (Ae. albopictus, Diptera: Culicidae), with the 50% lethal doses being 65.32, 61.47, and 65.91 mg/L for immature, semi-mature, and mature CRB EO, respectively. CRB EO was able to inhibit acetylcholinesterase and three detoxification enzymes, significantly reduce the diversity of internal microbiota in mosquitoes, and decrease the relative abundance of core species within the microbiota. The present results may provide novel insights into the utilization of plant-derived essential oils in anti-mosquitoes.